The Effectiveness of Canvas Media-Based Mind Mapping Model on Learning Poetry Writing Skills of Elementary School Students - Mezzaluna Safro, Rizatul; Zulikhatin Nuroh, Ermawati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study is to determine the effectiveness of the Canva-assisted Mind Mapping learning model in writing poetry for fifth-grade students in the Muhammadiyah 5 Porong Elementary School 2022/2023 academic year. The research method used was quantitative. This research was a pre-experimental design with a one-group pretest-posttest design model. The population of this study was all students in Class V at SD Muhammadiyah 5 Porong, totaling 22 students. The sample in this study is saturated because the total population is less than 30, that is, 22 students. Data were collected from primary and secondary sources. The primary data are in the form of poetry-writing test results in the form of pre-test and post-test according to the selected sample, while the secondary data in this study are in the form of documentation in the form of photos and data on the number of samples. The data collection technique in this study was a poetry-writing test in the form of a pre-test, post-test, and documentation. The data analysis techniques used were the normality test, homogeneity test, t-test, and N-gain test. The results showed that the mind-mapping learning model is effective for application in the poetry-writing skills of fifth-grade students at SD Muhammadiyah 5 Porong. This is proven by 90% of the N-gain value in the mind mapping model. The inferential test on the independent sample test is known to be Sig (2-tailed) with a value of 0.000. The output data shows that HO is rejected, whereas Ha is accepted. It is concluded that the hypothesis test shows that there are differences in the results of the pre-test and post-test of the mind mapping model in learning poetry-writing skills.